2021
DOI: 10.1038/s43017-021-00195-3
|View full text |Cite
|
Sign up to set email alerts
|

Causes, impacts and patterns of disastrous river floods

Abstract: River floods caused about 7 million fatalities in the twentieth century 1 , and their direct global average annual loss (AAL) is estimated at US$ 104 billion (2015Exposure to floods is expected to grow by a factor of three by 2050 owing to increases in population and economic assets in flood-prone areas 3 . Depending on the socio-economic scenario, human losses from flooding are projected to rise by 70-83% and direct flood damage by 160-240% relative to 1976-2005, with a temperature increase of 1.5 °C (ref. 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
191
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(201 citation statements)
references
References 221 publications
(258 reference statements)
3
191
0
7
Order By: Relevance
“…This initial data screening resulted into 161 gauges (483 catchment-season case studies) retained for analysis, whose geographical locations are shown in figure 1(G). The Mann-Kendall test applied to seasonal maxima identified significant (p < 0.01) trends in only a marginal fraction (3%) of the case studies, confirming the absence of flood trends for this region highlighted by [46].…”
Section: Benchmarking Phev Against Leading Methods For Flood Hazard Assessmentmentioning
confidence: 51%
“…This initial data screening resulted into 161 gauges (483 catchment-season case studies) retained for analysis, whose geographical locations are shown in figure 1(G). The Mann-Kendall test applied to seasonal maxima identified significant (p < 0.01) trends in only a marginal fraction (3%) of the case studies, confirming the absence of flood trends for this region highlighted by [46].…”
Section: Benchmarking Phev Against Leading Methods For Flood Hazard Assessmentmentioning
confidence: 51%
“…We focused here on the link between precipitation clustering and high discharge. Still, whether high discharge translates into a flood, particularly a disastrous one, depends on many other factors, like antecedent catchment wetness, the presence of infrastructure and its management, or the timing of precipitation across the catchment (Merz et al, 2021). These factors can also interact across various spatial and temporal scales, depending on the flood event.…”
Section: Link To High Discharge Processesmentioning
confidence: 99%
“…Flood is the most destructive natural hazard in the world. It adversely impacts the environment and human life, especially in flood-prone areas, causing environmental, societal, and economic losses such as water pollution, crop failure, casualties, health problems due to water-borne and vector-borne diseases, infrastructure damages (e.g., buildings, roads, power supplies, telecommunications), and economic activity disruption (Rosyidie, 2013;Bubeck et al, 2017;Kheradmand et al, 2018;Sholihah et al, 2020;Merz et al, 2021). It was estimated that around 21 million people are affected by river floods worldwide annually, and the number can increase to 54 million people in 2030 due to climate change and socio-economic development (Ward et al, 2013;Winsemius et al, 2013;Luo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%